Application of the RtI Model in Learning Disability Diagnosis: Perceptions of Current Practices by New Jersey Special Education Administrators - Lowry, Pamela E. (Journal of the American Academy of Special Education Professionals, 2013)
This paper examines current practices in implementing a Response to Intervention (RtI) in diagnosing specific learning disabilities. The use of the aptitude achievement discrepancy model, RtI model or a combination is reviewed. A survey of special education administrators in New Jersey compares methods of identification and consistency of application across districts. Findings indicate that few districts are currently implementing RtI along with the discrepancy model in determining eligibility with a specific learning disability. No district is using RtI as the sole determinant for this classification category. RtI models differ across districts with no consistency in interventions or screening tools.